Importance of visual and proprioceptive inputs for maintaining balance in patients with chronic non-specific neck pain: A cross-sectional study - Wenwen Wei; Wenxiang Li; Yixin Wang; Shuohan Zhang; Guoqiang Fan; Yiwen Bai (PLoS ONE, 2026)
Objective The aim of this study was to investigate the differences in muscle activation among patients with chronic non-specific neck pain (CNSNP) when performing resistance movements in different sensory inputs in a sitting position, using surface electromyography (sEMG) as an indicator. Materials and methods A total of 39 participants with CNSNP were recruited. sEMG recordings of the respective cervical muscles were measured for participants seated on four surface categories: eyes-closed-dynamic-surface, eyes-open-dynamic-surface, eyes-closed-stable-surface and eyes-open-stable-surface during neck extension, flexion, left and right lateral flexion, left and right rotation. Muscle activities in each situation were conducted thrice times and normalized as the percentage of maximum voluntary contraction (%MVC). Results Two-factor repeated measures analysis of variance (ANOVA) of the study data showed that the MVC% of respective muscles when seated on a dynamic surface was significantly lower compared with that recorded when seated on a stable surface, for the movements of extension (p = 0.012), flexion(p < 0.001), left lateral flexion(p = 0.001), right lateral flexion(p < 0.001) and left rotation(p = 0.0163). Simple effect analysis of the study data showed that the MVC% recorded for right rotation when seated on an eyes-closed-dynamic surface was lower than those recorded in the other three surface categories. Conclusion In this study, different sEMG activities of cervical muscles were identified under different sensory inputs in patients with CNSNP. This sheds light on the sensory integration and compensatory mechanisms in patients with CNSNP, and helps to guide their clinical management.